Sucrose concentration alters the physiological potential of in vitro germinated gabiroba seeds - Souza, Geiciane Cintra de; Dias, Lana Laene; D’Abadia, Ana Claudia Alves; Stein, Vanessa Cristina; Silva, Givanildo Zildo da; Machado, Carla Gomes; Reis, Edésio Fialho do; Rocha, Diego Ismael; Netto, Antônio Paulino Costa (Plant Cell Culture & Micropropagation - ISSN 1808-9909, 2021)
The propagation of gabiroba occurs via sexual reproduction. However, their seeds are recalcitrant. The objective of this study was to evaluate the physiological quality of Campomanesia adamantium and C. pubescens seeds, sown in a growth medium with different sucrose concentrations, to understand the performance of these species in an in vitro environment. An entirely randomized design was used in a 2x4 factorial scheme [2 species and 4 doses of sucrose (0, 20, 40 and 80 g L-1)]. The following were evaluated: germination, growth emergence and parameters and development of seedlings. The presence of sucrose in the culture environment did not improve the germination percentage. C. adamantium seeds germinated in supplemented environment with up to 20 g L-1 showed higher emergence and vigor and considerable increase in the number and length of the roots. For C. pubescens, the culture environment without the addition of sucrose provided better results.